IMPLEMENTASI SIRKULAR EKONOMI MELALUI PEMANFAATAN LIMBAH RUMAH TANGGA UNTUK BUDIDAYA MAGGOT - Haqqi, Zainul; Diana, Anita; Aziz, Azmi; Ramdhani, Bayu; Arini, Baiq Alfina Dwi; Rahmatin, Aulia Sartika; Toriqurrahman, Muhammad; Ananda, Laras Rezky; Deftiansyah, Rudi; Adawiah, Sulistial; Ramdani, Nova; Raihan, Raihan; et al. (Jurnal Warta Desa (JWD), 2023)
The issue of household waste in Indonesia, particularly organic waste, is increasingly severe due to rapid population growth and urbanization. In efficient waste management has led to various negative environmental impacts, such as pollution and increased greenhouse gas emissions. One promising solution to address this problem is utilizing Black Soldier Fly (BSF) larvae, or maggots, which have remarkable abilities to decompose organic waste and transform it into high-value products like animal feed and organic fertilizer. This initiative aims to explore the life cycle of BSF maggots, from eggs to adult flies, and the factors influencing their growth, such as feed media, temperature, humidity, and nutrient content, using household waste as feed. Observations indicate that optimal environmental conditions, such as a temperature of around 30°C and humidity above 60%, significantly support egg production and larval growth. Additionally, organic media rich in nutrients, such as fish and chicken meat waste, can enhance the protein content in maggots, making them beneficial for animal feed sustainability. BSF cultivation requires specialized facilities, such as enclosures with supporting equipment, to facilitate mating and egg-laying processes. By optimizing BSF maggot management, organic waste can be efficiently handled, reducing negative environmental impacts and producing valuable products for animal feed and organic fertilizer. This supports food security and sustainable agriculture in Indonesia.